GE_GERICHTE P/5792/2005 vom 30. September 2014 - GE Cour de justice (2014)
DROIT TRANSITOIRE; ACTE D'ACCUSATION; DÉBAT(EN GÉNÉRAL); PRINCIPE DE L'ACCUSATION; COAUTEUR(DROIT PÉNAL); INSTIGATION; ABUS DE CONFIANCE; AUDITION OU INTERROGATOIRE; TÉMOIN | CPP.448; CPP.450; CPP.9; CPP.325.1; CPP.429; CP.139; aCstGe.36; aCPP.379; aCPP.134; aCPP.283